Two Mechanisms One Molecule: Developing a ‘Truly’ Bifunctional Degrader Targeting Rpn13 and CRBN - Cody A. Loy; Shawn E. Vinogradsky; Darci J. Trader (Journal of the American Chemical Society, 2026)
Abstract Targeted protein degradation (TPD) has emerged as a powerful strategy to eliminate disease-relevant proteins, yet current approaches remain largely constrained to hijacking ubiquitin ligases. We previously introduced ByeTACs, bifunctional molecules that directly recruit proteins to the proteasome for E-ligase independent degradation. Here, we report “Truly” degraders, a new class of dual-mechanism molecules that combine a ligand for the proteasomal receptor Rpn13 with a ligand for cereblon (CRBN) to simultaneously engage both ubiquitin-independent and ubiquitin-dependent degradation pathways. Structure-guided design identified an optimal linker length that supports efficient substrate processing, with the PEG4 derivative (Truly-4) inducing robust depletion of both Rpn13 and CRBN in several cancer cell types. Remarkably, Truly-4 is the first noncovalent small molecule shown to degrade full-length Rpn13, a target previously approached using covalent or domain-restricted strategies. Mechanistic studies confirmed that degradation of Rpn13 proceeds via CRBN-dependent E3 ligase activity, whereas CRBN degradation occurs through an E-ligase independent process, consistent with a ByeTAC mechanism. Importantly, Truly-4 induces selective cytotoxicity in hematologic and solid cancer cell lines but not in healthy cells, despite comparable Rpn13 depletion, indicating that dual degradation can uncouple target engagement from toxicity. These findings establish a generalizable framework for engineering bifunctional degraders that program the proteasome to execute parallel degradation mechanisms and highlight proteasome receptors as druggable nodes for selective destruction of disease-relevant proteins.